Alternative method to facilitate resolution of paraphimosis after penile trauma in the horse. (9th March 2016) - De Brouwer, E.; Ribera, T.; Climent, F.; Prades, M.
Summary: Inflammation associated with traumatic injury to the penis is characterised by pain, heat and oedema. Ensuing penile swelling interferes with retraction of the penis into the prepuce, resulting in paraphimosis. This report describes the use of a 5 l capacity pressure infusion bag to reduce penile oedema in three horses. This technique provided complete resolution of oedema and associated paraphimosis in approximately 1 h. The use of the bag, along with an abdominoinguinal bandage, a plastic funnel suspensory device, or a penile repulsion device (Probang) to avoid recurrence, offers a novel treatment that may be performed with the horse sedated.